Hydrochemical zonation and depth-based vulnerability of groundwater in Islamabad using GIS and WQI techniques - Shinwari, Fayaz Ullah; Liaquat, Urooj; Khan, Mumtaz Ali; Kontakiotis, George; Makri, Panayota; Lianou, Vasiliki; Antonarakou, Assimina (Frontiers in Water, 2025)
In Islamabad, groundwater is an essential resource that supports industrial, agricultural, and home use despite growing demand and fast urbanization. However, worries about anthropogenic influences causing its quality to decline make region-specific assessment necessary for sustainable management. This work uses an integrated strategy that combines field sampling, GIS-based spatial interpolation, and Water Quality Index (WQI) analysis to evaluate the hydrochemical properties and geographical variability of groundwater quality in Islamabad. 37 borewell samples in all were gathered, examined for physico-chemical characteristics, and their WQI values were calculated. The findings showed that, for drinking purposes, 5.41% of samples were rated as “Excellent,” 86.49% as “Good,” and 8.11% as “Poor.” Inverse Distance Weighted (IDW) interpolation was used to estimate the depth of the water table spatially. The results showed that the depth varied between 25 and 399 feet, with shallower zones signaling enhanced accessibility and recharging, while statistical analysis revealed only a weak association between depth and water quality, suggesting additional factors contribute to contamination. No significant linear trends were found by depth-wise hydrochemical regression, however elevated quantities of sulfate, carbonate (CO₃2−), sodium carbonate (Na₂CO₃), and Nitrates (NO₃−) were found in shallow aquifers by depth-wise hydrochemical investigation, indicating the influence of fertilizer leaching or surface activities. The geochemical evolution with depth was demonstrated by the increasing quantities of sodium bicarbonate (NaHCO₃), chloride (Cl−), and sodium chloride (NaCl) found in deeper aquifers. Notably, because of the higher concentrations of TDS, EC, chloride, and Nitrates, the Tarnol region displayed the highest risk of contamination. In addition to highlighting the necessity of depth-informed aquifer protection and land use restriction to guarantee long-term water security for Islamabad’s expanding population. The results of statistical regression provide additional support for these conclusions, demonstrating the intricacy of the factors influencing groundwater contamination and emphasizing the necessity of multivariate techniques in future monitoring plans.